Perbedaan Keterampilan Pemecahan Masalah Pada Pembelajaran Fisika Menggunakan Metode Problem Posing dan Problem Solving - Rahman, Adetya; Hartini, Sri (Universitas Lambung Mangkurat, 2015)
Teachers should be able to choose the method of learning that can help students in learning physics, namely the method of problem posing and problem-solving method. The purposes of this study are : (1) describe the learning physics skills by using problem posing method, (2) describe the learning physics skills by using problem solving method, and (3) know difference between learning physics skills by using problem posing method and problem solving method in class XI of Science SMAN 6 Banjarmasin. The type of this research is quasi experimental study. The sample consists of two groups, there are class of experiment I (class XI IPA 2) , and class of experiment II (class XI IPA 1) at SMAN 6 Banjarmasin. Data collection techniques are test and documentation. Data analysis uses prerequisite analysis, normality test and homogeneity test, then F test. The results of the research show: (1) learning physics skill that uses problem posing method has average 76,1Â it is in good qualification, (2) learning physics skill that uses problem solving method has average 83,6Â it is in good qualification too, and (3) the result of hypothesis examine shows that a difference in learning physics skill, which the value of probability in F test of learning physics skills is 0,013 < 0,05 that H0 is rejected, it means that there are difference in learning physics skill between the experiment class 1 and experiment class 2 on impulse and momentum material.Â